Comparative effectiveness of advanced wound dressings for patients with chronic venous leg ulcers: A systematic review. Issue 2 (March 2014) - Valle, M. Frances; Maruthur, Nisa M.; Wilson, Lisa M.; Malas, Mahmoud; Qazi, Umair; Haberl, Elisabeth; Bass, Eric B.; Zenilman, Jonathan; Lazarus, Gerald
Abstract The purpose of this study was to systematically review the literature on the benefits and harms of advanced wound dressings on wound healing, mortality, quality of life, pain, condition of the wound bed, and adverse events for patients with chronic venous leg ulcers as compared with treatment with compression alone. We searched for primary studies in the databases of MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, and the Cumulative Index to Nursing and Allied Health Literature® from January 1980 through July 2012. Each study title, abstract, and full article was evaluated by two independent reviewers. Thirty‐seven studies met our specific search criteria, although most evidence was of low or insufficient quality. Cellular dressings, collagen, and some antimicrobial dressings may improve healing rates of chronic venous leg ulcers vs. compression alone or other dressings. Limited data were available on other outcomes. The poor quality of the literature limits conclusions and necessitates future, well‐conducted studies to evaluate the effectiveness of advanced wound dressings on chronic venous ulcers.